Equalization of Opportunity: Definitions, Implementable Conditions and Application to Early-Childhood Policy Evaluation - Francesco Andreoli; Tarjei Havnes; Arnaud Lefranc (Institute for the Study of Labor (IZA), 2014)
This paper develops a criterion to assess equalization of opportunity that is consistent with theoretical views of equality of opportunity. We characterize inequality of opportunity as a situation where some groups in society enjoy an illegitimate advantage. In this context, equalization of opportunity requires that the extent of the illegitimate advantage enjoyed by the privileged groups falls. Robustness requires that this judgement be supported by the broadest class of individual preferences. We formalize this criterion in a decision theoretic framework, and derive an empirical condition for equalization of opportunity based on observed opportunity distributions. The criterion is used to assess the effectiveness of child care at equalizing opportunity among children, using quantile treatment effects estimates of a major child care reform in Norway.
Keywords: D63; J62; C14; I24; 330; equality of opportunity; public policy; inverse stochastic dominance; economic distance; income distribution; child care; pre-school